Non‐Detection of Lightning During the Second Parker Solar Probe Venus Gravity Assist. Issue 8 (26th April 2021) - Pulupa, Marc; Bale, Stuart D.; Curry, Shannon M.; Farrell, William M.; Goodrich, Katherine A.; Goetz, Keith; Harvey, Peter R.; Malaspina, David M.; Raouafi, Nour E.
Abstract: The Parker Solar Probe (PSP) spacecraft completed its second Venus gravity assist maneuver (VGA2) on December 26, 2019. For a 20 min interval surrounding closest approach, the PSP/FIELDS Radio Frequency Spectrometer (RFS) was set to "burst mode, " recording radio spectra from 1.3 to 19.2 MHz at sub‐second cadence. We analyze this burst mode data, searching for signatures of radio frequency "sferic" emission from lightning discharges. During the burst mode interval, only four spectra were observed with strong impulsive signals, and all four could be attributed to saturation of the RFS high gain stage by in situ electrostatic plasma waves. These RFS measurements during VGA2 are consistent with previous non‐detection of radio frequency lightning signals from Venus reported by Gurnett et al. (2001, https://doi.org/10.1038/35053009 ). Plain Language Summary: The Parker Solar Probe (PSP) studies the physics of the solar wind, using an elliptic solar orbit which brings it much closer to the Sun than any other spacecraft. PSP uses seven Venus flybys to change its orbital trajectory via gravitational assist, lowering the distance of closest solar approach after each flyby. During Venus Flyby 2 in December 2019, the PSP radio receiver was set to a special operating mode, which is sensitive to possible lightning signals from the Venus atmosphere. During the flyby, no lightning signals were detected. This is consistent with previous non‐detection of Venus lightning at radio frequencies reported by Gurnett et al. (2001). Key Points: During the second Parker Solar Probe (PSP) Venus gravity assist, the PSP/FIELDS radio receiver recorded high cadence "burst mode" spectra We examined the burst mode data for lightning‐associated emission. No lightning events were observed, consistent with prior observations We can use this non‐detection to place an upper limit on possible lightning emission from Venus